Development of a Case Method-Based Balaghah Learning Module: A Solution to Improve Students’ Understanding of Balaghah Science - Ulum, Fatkhul; Hukom, Julham; Haruna, Haruna Abubakar; Irawan, Bambang; Huda, Mokhammad Miftakhul; Mariana, Mariana (FKIP Universitas Lampung, 2025)
Development of a case method-based Balaghah learning module: a solution to improve students’ understanding of Balaghah science. The development of technology in the world of education encourages the development of innovative learning media that can transform abstract materials into more concrete ones and encourage student involvement. Objective: The objective of this study is to develop a Balaghah learning module based on the case method that is feasible, practical, and effective to improve students' understanding of Balaghah science. Method: This study is a development research using the ADDIE development model. This study involved 76 students of the Arabic Language Education Study Program, Makassar State University, who were selected using a purposive sampling technique. Data collection techniques in this study include interviews, validation, observation for the implementation of learning, and Balaghah understanding tests. Data were analyzed quantitatively using descriptive statistics and inferential tests, and supported by qualitative analysis. Findings: Our research findings indicate that the developed case method-based Balaghah learning module is valid, practical, and effective in improving students' understanding of Balaghah. The feasibility of this case method-based Balaghah learning module is demonstrated through assessments by media experts (91%) and material experts (95%). The practicality of the case method-based Balaghah learning module is supported by lecturers’ assessment (90%), small-scale trials (92%), and large-scale trials (91%). In addition, the effectiveness analysis using a quasi-experimental design produced a t-test of 5.18 and a significance value less than 0.05. Meanwhile, the effect size of (d = 2.45; P < 0.05) indicates a strong impact. Conclusion: The case method-based Balaghah learning module has proven effective in improving students' understanding of Balaghah. Integrating a case method-based approach into Balaghah teaching can be an innovative strategy for making learning more concrete, contextual, and meaningful. Keywords: arabic, balaghah, case method, learning module.